2016
DOI: 10.1002/asl.685
|View full text |Cite
|
Sign up to set email alerts
|

Lightning activity in the Mediterranean: quantification of cyclones contribution and relation to their intensity

Abstract: A 10-year data set of intense Mediterranean cyclones was used for a twofold objective: first to quantify the cyclone's contribution to lightning occurrence in the region and second to investigate potential connection of lightning with cyclones intensity. For this reason, we used cyclone tracks, lightning observations and reanalysis from the European Centre for Medium Range Weather Forecasts, for the 10-year period of 2005-2014. Results showed that intense cyclones provoke <10% of lightning activity over the Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…Galanaki et al . () showed that intense cyclones associated with lightning activity present their highest lightning activity on average about 6 hr prior to the maximum intensity, whilst similar studies for tropical cyclones and hurricanes show a temporal lag of 24–30 hr before their maximum intensity (Price et al, ; Zhang et al, ).…”
Section: Evolution Of the Tlc Between The Sixth And Ninth Of Novembermentioning
confidence: 88%
“…Galanaki et al . () showed that intense cyclones associated with lightning activity present their highest lightning activity on average about 6 hr prior to the maximum intensity, whilst similar studies for tropical cyclones and hurricanes show a temporal lag of 24–30 hr before their maximum intensity (Price et al, ; Zhang et al, ).…”
Section: Evolution Of the Tlc Between The Sixth And Ninth Of Novembermentioning
confidence: 88%
“…A plausible explanation might reside in the sharp sea-land transitions, where the influence of geographical elements might perturb total column water vapour and rainfall, as well as in the specificity of Mediterranean cyclones, where convection is not common in cyclone's centre. Indeed, Galanaki et al (2016) showed that only one third of intense Mediterranean cyclones might present lightning activity close to their centre. Therefore, one could not expect for the total of Mediterranean cyclones that convection would be related to cyclones' intensification through the release of latent heat and increased rainfall due to high water vapour content in the atmosphere.…”
Section: Quantification Of Cyclone Rainfallmentioning
confidence: 99%
“…However, convective rainfall was produced in the core of four cyclones and at the cold front of two. In a climatological framework, Galanaki et al (2016) used lightning observations to address the issue of DC in cyclone cores. Their results suggest that about one third of intense cyclones may develop DC close to their centre, while, in the other two thirds, no lightning was observed at all.…”
Section: Introductionmentioning
confidence: 99%
“…From the late summer on, lightning activity moves gradually to the coast and offshore, where the activity is dominant in autumn. This change is related to the average land/sea temperature difference, the average sea surface temperature being warmer during autumn compared to land (Kotroni and Lagouvardos, 2016;Galanaki et al, 2018).…”
Section: Lightning Activity In the Region Of Interestmentioning
confidence: 99%